(untitled) - Hall, Peter (London, 1988)
Part one The Kondratieff waves; Part two The mechanical age: New IT in the second Kondratieff, 1846-95; Part three The electrical age: New IT in the third Kondratieff, 1896-1947
Keywords: Technological innovations,Đổi mới công nghệ; Economic aspects,History,Lịch sử,Khía cạnh kinh tế